Effects of boat-type parameters of boat-type tractor on working resistance and subsidence depth - WANG Yongwei; HE Zhuoliang; WANG Jun (浙江大学学报. 农业与生命科学版)
In order to investigate the effects of structural and working parameters on the working resistance and subsidence depth of boat-type tractor in paddy field, simplified prototypes of boat-type tractors with testing system were developed. Ground ratio pressure, working speed, curvature radius of board, ground contact angle and depth of surface water of paddy soil were taken as factors, and working resistance and subsidence depth were taken as evaluation indexes. The experiments were conducted through the paddy soil platform which was filled with filtered silt loam. Results showed that all the factors had significant effects on the two evaluation indexes. The working resistance and subsidence depth increased monotonously with the increase of ground ratio pressure within 250-350 kg/m2. However, when the ground ratio pressure was beyond 300 kg/m2, the increase of two evaluation indexes was much slower. When working speed, curvature radius of board and ground contact angle were within 0.2-1.0 m/s, 300-500 mm and 25.0°-35.0°, respectively, the working resistance and subsidence depth increased after a slight decrease on the whole. The working resistance and subsidence depth reached the minimum values at the working speed of 0.6 and 0.8 m/s, respectively; and subsidence depth and working resistance reached the minimum values with ground contact angle of 27.5° and 30.0°, respectively. When the depth of surface water of paddy soil increased within 10-50 mm, the subsidence depth decreased monotonously, while the working resistance increased after a slight decrease on the whole. The working resistance reached the minimum value with the depth of surface water of 20 mm. In conclusion, the optimum working and structural parameters for boat-type tractors in paddy field are 0.6-0.8 m/s for working speed, 350-450 mm for curvature radius of board, 27.5°-30.0° for ground contact angle, and 20-40 mm for depth of surface water. The result can provide references for the design and operation of boat-type tractor in paddy field.